Respostas

A melhor resposta!
2014-04-21T18:23:11-03:00
6) dada a função f:IR->IR definida por f(x) = - 4x + 3, determine o valor de x para que:
a) f(x) = - 4                                            b)f(x)= 1/2
f(x) = -4x + 3
f(x) = - 4

Assim

f(x) = - 4x + 3     é só substituir o f(x) = -4
 -4  = - 4x + 3
- 4 - 3 = - 4x
    - 7  = - 4 x
-4x = - 7
x = - 7/ - 4
x = 7/4


f(x) = -4x +3
b)f(x)= 1/2   só substituir o f(x) = 1/2

f(x)  = - 4x + 3
1/2  = - 4x + 3
1/2 - 3 = - 4x

1 - 6 = - 8x
----------------
       2

1 - 6 = -8x
- 8x = 1 - 6
- 8x = - 5
x = -5/-8 
x = 5/8




1 5 1